Dynamic reorganization of multivesicular bodies and exosome production impacted by sonoporation - Weiping Li; Najla A. Saleh; Connie Gao; Matthew A. Gagea; Xheneta Vitija; Masamitsu Kanada; Cheri X. Deng (Scientific Reports)
Abstract Naturally occurring cell-derived extracellular vesicles (EVs) have emerged as attractive nanocarriers for drug delivery. However, production of large quantities of EVs for clinical applications in a scalable manner remains a significant challenge. This study investigated at the single cell level how sonoporation, or membrane poration produced by ultrasound-induced microbubble cavitation, impacts EV production using mouse macrophage RAW 264.7 cells stably expressing CD63-GFP as a model system. Real-time fluorescence videomicroscopy detected rapid changes in CD63-GFP, a tetraspanin family member highly enriched in intraluminal vesicles tagged with GFP, to track changes in multivesicular bodies (MVBs), which are the cellular compartments where exosomes originate within the cells. Our results revealed distinct dynamic changes in CD63-GFP intensity and distribution in RAW 264.7 cells in terms of response time and duration depending on whether the cells were directly or indirectly impacted by sonoporation, suggesting reorganization of MVBs in response to direct and indirect mechanisms resulted from the mechanical impact of ultrasound pulse on the cells. Analysis of the supernatant from sonoporation-treated RAW 264.7 cells expressing CD63-GFP demonstrated a delayed and sustained increase in the production of CD63-GFP-positive EVs. These results show the robust and detailed effect of sonoporation and reveal insights into sonoporation-induced EV release useful for guiding the application of sonoporation to enhance large-scale EV production.